A Fiqh Analysis Of Istibdal Waqf Practices In Indonesia: Analisis Fikih Tentang Istibdal Praktek Wakaf Di Indonesia - Syamsuri, Syamsuri; Dyani Hidayat, Salsa Addella (DAS Institute, 2026)
Waqf plays an important role in the Islamic economic system, both spiritually and socially. However, socio-economic dynamics often make some waqf assets unproductive. To address this, istibdal (the replacement of waqf assets) is seen as a solution to maintain sustainability and public benefit. This article discusses the practice of istibdal in Indonesia from both fiqh and regulatory perspectives. In fiqh, scholars differ in opinion, ranging from those who prohibit it to those who permit it under the condition of public interest (maslahah). Legally, istibdal is regulated under Law No. 41/2004, Government Regulation No. 42/2006, and MUI fatwas, with supervision by BWI and the Ministry of Religious Affairs. Nevertheless, its implementation still faces challenges such as bureaucracy, low awareness among nazhir (waqf managers), community resistance, and the risk of misuse. Strengthening capacity, ensuring transparency, and encouraging community participation are needed so that istibdal aligns with maqāṣid al-sharī‘ah and supports productive and sustainable waqf governance.